Trophic interactions between brown and south polar skuas at Deception Island, Antarctica - Graña Grilli, Maricel; Montalti, Diego (Polar Biology)
It is broadly accepted that the brown skua (Stercorarius antarcticus lonnbergi) competitively excludes the south polar skua (S. maccormicki) from penguin colonies when breeding sympatrically, forcing the latter to feed on marine resources. The purpose of this work was to examine the diets and trophic niche breadths of each species where they co-occur and to determine the degree of overlap. To this end, we analyzed 169 pellets of brown skuas, collected in two different areas (20 individuals), and 152 of south polar skuas, collected in three different areas (18 individuals), on Deception Island, South Shetland Islands, Antarctica, during the austral summer 2000. Pellet analysis often underestimates the amount of easily digestible prey, but allows for comparisons of the relative contributions of different items in the diet. South polar skuas at our study locations consumed seven different food items and had a trophic niche breadth of 0. 133 compared to brown skuas that fed on 10 different items and had a trophic niche breadth of 0. 078. The niche overlap between the species was 82. 1%. Penguins were the principal food source of both species, however, brown skuas fed mostly on chicks, while south polar skuas fed on adults (carcasses). The use of different age classes of penguins as a food source offers an alternative to competitive exclusion, allowing the coexistence of these species on Deception Island. © 2011 Springer-Verlag. Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Montalti, Diego. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina